Ответ:
(2; -2)
Объяснение:
х=8+3у
2*(8+3у)-у=6
16+6у-у=6
5у=6-16
5у=-10
у=-2
х=8+3*(-2) = 2
(2;-2)
х-3у=8
2х-у=6
----------
Підставляємо х у друге рівняння:
2(8+3у)-у=6
Знаходимо х:
х=8+3*(-2)
х=2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(2; -2)
Объяснение:
х=8+3у
2*(8+3у)-у=6
16+6у-у=6
5у=6-16
5у=-10
у=-2
х=8+3*(-2) = 2
Verified answer
Ответ:
(2;-2)
Объяснение:
х-3у=8
2х-у=6
----------
х=8+3у
2х-у=6
----------
Підставляємо х у друге рівняння:
2(8+3у)-у=6
16+6у-у=6
5у=-10
у=-2
Знаходимо х:
х=8+3*(-2)
х=2